Electrical tree inception voltage and propagation in XLPE containing silica nanoﬁller - Nazatul Shiema, Mohd Nazar; Noor Syazwani, Mansor; Khayam, Umar; Amir Izzani, Mohamed; Nor Asiah, Muhamad; Mariatti, Jaafar; Mohamad Kamarol, Mohd Jamil (Springer Science and Business Media Deutschland GmbH, 2022)
This paper presents the tree inception voltage and electrical tree propagation in XLPE containing silica nanofiller. The concentration of silica nanofillers in XLPE was 0 wt%, 0.5 wt%, 1.0 wt%, 1.5 wt% and 1.75 wt%. The needle plate electrodes were used to analyzed the tree inception voltage and electrical treeing propagation. The structure and the propagation length of electrical tree growth were analyzed after 20 min of tree inception voltage. The result of tree inception voltage and the electrical tree propagation in XLPE containing silica nanofiller was compared with pure XLPE composite. The silica nanofiller with the concentration of 1.5 wt% revealed the higher TIV and slower propagation of electrical tree in the XLPE nanocomposite.